Resting metabolic rate and energy intake in female gymnasts, figure-skaters and soccer players - Fogelholm, G. M.; Kukkonen-Harjula, T. K.; Taipale, S. A.; Sievanen, H. T.; Oja, P.; Vuori, I. M. (International Journal of Sports Medicine, 1995)
We examined the hypothesis that lean female athletes, as compared to other female athletes and controls, have a greater deficit between reported energy intake (EI) and estimated energy expenditure (EE), and a reduction in resting energy expenditure adjusted to fat free and fat masses (REEADJ). The subjects were 12 gymnasts and figure-skaters (lean athletes), 12 soccer players (normal-weight athletes) and 10 normal-weight, untrained, controls. Body composition was calculated from a 3-compartment model (underwater weighing and dual energy x-ray absorptiometry). REE was assessed by indirect calorimetry. Physical activity and EI were estimated from 7-day records. EE was calculated using activity records and REE. REEADJ was similar in all groups (p > 0.05). EI was 8.29 (SD 1.84), 7.04 (SD 2.23) and 8.95 (SD 1.68) MJ.d-1 in controls, gymnasts and soccer players, respectively (p = 0.06). In gymnasts, reported EI was 3.19 (SD 2.63) MJ.d-1 lower than estimated EE. EI minus EE in controls was -0.18 (SD 1.80; different from gymnasts, p < 0.01) MJ.d-1, and in soccer players -0.47 (SD 1.89; different from gymnasts, p < 0.05) MJ.d-1. Low reported energy intake in gymnasts might reflect their attitudes on diet and body image.